A GENOME‐WIDE ASSOCIATION STUDY OF CLINICAL SYMPTOMS OF DISSOCIATION IN A TRAUMA‐EXPOSED SAMPLE. Issue 4 (27th March 2014) - Wolf, Erika J.; Rasmusson, Ann M.; Mitchell, Karen S.; Logue, Mark W.; Baldwin, Clinton T.; Miller, Mark W.
<x xml:space="preserve">Abstract</x> Background Recent work suggests that a subset of individuals with posttraumatic stress disorder (PTSD) exhibit marked dissociative symptoms, as defined by derealization and depersonalization. A dissociative subtype of PTSD was added to the diagnostic criteria listed in the Diagnostic and Statistical Manual of Mental Disorders, Version 5 (DSM‐5) to capture this presentation of PTSD. This study examined genetic polymorphisms for association with the symptoms that define the dissociative subtype of PTSD using a genome‐wide approach. Methods The sample comprised 484 White, non‐Hispanic, trauma‐exposed veterans and their partners who were assessed for lifetime PTSD and dissociation using a structured clinical interview. The prevalence of PTSD was 60.5%. Single‐nucleotide polymorphisms (SNPs) from across the genome were obtained from a 2.5 million SNP array. Results Ten SNPs evidenced suggestive association with dissociation (P < 10−5). No SNPs met genome‐wide significance criteria (P < 5 × 10−8). The peak SNP was rs263232 (β = 1.4, P = 6.12 × 10−7), located in the adenylyl cyclase 8 (ADCY8) gene; a second SNP in the suggestive range was rs71534169 (β = 1.63, P = 3.79 × 10−6), located in the dipeptidyl‐peptidase 6 (DPP6) gene. Conclusions ADCY8 is integral for long‐term potentiation and synaptic plasticity and is implicated in fear‐related learning and memory and long‐term memory consolidation. DPP6 is critical for synaptic integration and excitation. These genes may exert effects on basic sensory integration and cognitive processes that underlie dissociative phenomena.